Reductions in extracellular vesicle-associated microRNA-126 levels in coronary blood after acute myocardial infarction: A retrospective study - Yuan, Yujuan; Ma, Yiping; Aili, Zulipiya; Nijiati, Muyesai (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute Myocardial Infarction (AMI) is a kind of cardiovascular disease with high mortality and incidence. Extracellular vesicles (EVs) and microRNA-126 (miR-126) are known to play important role in the development and prognosis of several cardiovascular diseases. Therefore, this study aimed to investigate the changes in Extracellular vesicle (EV)-associated miR-126 levels in the coronary blood of patients with AMI to explore the relationship between miR-126 levels and AMI. Methods: We analyzed EV-associated miR-126 in the coronary blood of patients with AMI and stable coronary artery disease (SCAD) using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results: We tested the coronary blood of 20 patients with AMI and 20 with SCAD. The mean age of the patients was 58.8 ± 10.3 years and 32 (80%) were men. We observed that the EV -associated miR-126 levels were lower in patients with AMI (mean = 0.13; interquartile range: 0.08–0.22) than in patients with SCAD (mean = 0.37; interquartile range: 0.26–0.48) (P < 0.001). In addition, the levels of miR-126 were negatively associated with the Thrombolysis in Myocardial Infarction (TIMI) score (r = -0.66, P = 0.001). Conclusions: Reduction of EV-associated miR-126 levels in the coronary blood of patients with AMI may be involved in acute coronary thrombosis events.